De los miasmas a los edificios enfermos: hongos en el interior - Manzano Fernández, Aurora; Mancha García, Francisco De Borja (Revista Complutense de Ciencias Veterinarias, 2007)
The air quality has been an historical concern for humans. This was given expression to the term miasma by some pre-scientist doctrines, but today, pathologies as the sick building syndrome or the building related illness, closely related to indoor air quality, are been defined from science. Exposure to fungi plays a main roll in these processes etiologic: bad indoor conditions, high humidity above all, allow fungal growth, exposing the inhabitants to aeroallergens and organic dust that contains mycotoxines. In this work, we try to explain the exposure route and the pathogenicity mechanism involved.